VD_FINDINFO HC / 2016 / 505 vom 26. Mai 2016 - VD Tribunal cantonal (2016)
FARDEAU DE LA PREUVE, OBLIGATION D'ENTRETIEN, MESURE PROVISIONNELLE, MODIFICATIONEN GÉNÉRAL | 176 CC, 179 CC, 285 al. 1 CC, 8 CC